Pengaruh Pengetahuan Perpajakan, Sanksi Perpajakan, dan Pelayanan Fiskus Terhadap Kepatuhan Wajib Pajak - Diya Anggraeni Puspitasari; Prihasantyo Siswo (Jurnal Rekognisi Akuntansi, 2021)
The purpose of this study is to determine the effect of knowledge of taxation, tax sanctions, and special tax services on the compliance of individual taxpayers in carrying out their tax obligations, namely calculating, paying and reporting tax payable. The population in this study is the Individual Taxpayer (WPOP) in Gemilang Group. And the sample in this study is the population, which is 81 taxpayers. Data collection method with a questionnaire. The questionnaire was tested for validity and rebalance before collecting research data. The analysis technique in this study uses the classical assumption test, and multiple linear regression analysis. The results of this study indicate that tax knowledge has a negative effect on taxpayer compliance. This is evidenced by the value of the regression coefficient is negative -0.128 and tcount is smaller when compared to ttable (-0.909 <1.66515) at significance 0.000 <5%. Tax sanctions have a positive and significant impact on taxpayer compliance. This is evidenced by the positive value of the regression coefficient 0.336 and tcount is greater than the table (1.995> 1.66515) at significance 0.000 <5%. The tax authorities have a positive effect on taxpayer compliance. This is evidenced by the positive value of the regression coefficient 0.160 and the t-count is smaller when compared to the table (0.902 <1.66515) at significance 0.000 <5%.